Impact of Porous Media on Peristaltic Transport of Tangent Hyperbolic Nanofluid in Asymmetric Channel - Hashim, Aqeel J.; Abdulhadi , Ahmed M. (Iraqi Journal of Science, 2024)
The purpose behind this paper is to discuss nanoparticles effect, porous media, radiation and heat source/sink parameter on hyperbolic tangent nanofluid of peristaltic flow in a channel type that is asymmetric. Under a long wavelength and the approaches of low Reynolds number, the governing nanofluid equations are first formulated and then simplified. Associated nonlinear differential equations will be obtained after making these approximations. Then the concentration of nanoparticle exact solution, temperature distribution, stream function, and pressure gradient will be calculated. Eventually, the obtained results will be illustrated graphically via MATHEMATICA software.